2022
DOI: 10.1016/j.apsb.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The cGAS–STING signaling in cardiovascular and metabolic diseases: Future novel target option for pharmacotherapy

Abstract: The cyclic GMP–AMP synthase (cGAS)–stimulator of interferon genes (STING) signaling exert essential regulatory function in microbial-and onco-immunology through the induction of cytokines, primarily type I interferons. Recently, the aberrant and deranged signaling of the cGAS–STING axis is closely implicated in multiple sterile inflammatory diseases, including heart failure, myocardial infarction, cardiac hypertrophy, nonalcoholic fatty liver diseases, aortic aneurysm and dissection, obesity, etc. This is beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 213 publications
(324 reference statements)
0
56
1
Order By: Relevance
“…3 ). 305 309 Although the notion that obesity triggers chronic, low-grade inflammation has been recognized for decades, the pivotal role of the STING pathway in obesity has recently been appreciated. 310 312 The STING pathway can be activated by palmitic acid, leading to mitochondrial damage and thereby mtDNA leakage.…”
Section: Signaling Pathways In the Pathogenesis Of Obesitymentioning
confidence: 99%
“…3 ). 305 309 Although the notion that obesity triggers chronic, low-grade inflammation has been recognized for decades, the pivotal role of the STING pathway in obesity has recently been appreciated. 310 312 The STING pathway can be activated by palmitic acid, leading to mitochondrial damage and thereby mtDNA leakage.…”
Section: Signaling Pathways In the Pathogenesis Of Obesitymentioning
confidence: 99%
“…Accumulating pieces of evidence showed that a HFD could result in various forms of cardiac abnormalities, including cardiac inflammation, CH, and fibrosis ( Sorop et al, 2020 ; Wali et al, 2020 ; Zhang and Cai, 2020 ; Oduro et al, 2022 ); therefore, an HFD rat is an appropriate animal model for studying CH. We found that HFD rats revealed hallmarks of CH, including increased volume of cardiomyocyte size, upregulated expressions of ß -MHC and ANP ( Figure 2 ), and LV dysfunction ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…They induce cell cycle checkpoint activation, transcriptional feedbacks, DNA repair, and eventually apoptosis ( 32 ). In particular, transcriptional activation of sterile inflammatory-adaptive response is a typical DDR downstream event ( 33 ). Similarly, the pathological HF transcription program is enriched for pathways related to innate immune signaling converging on NFkB/RelA, and a pro-inflammatory response converging on TGFβ signaling module, leading to cellular matrix organization ( 34 ).…”
Section: Discussionmentioning
confidence: 99%